Polish Underground Extracts, no. 8 (1985) - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Extracts from Polish underground publications compiled and translated into English by the RFE Polish Publication Unit for broadcasting purposes. Introductions to most articles are provided by RFE staff, and items are compiled in issues based mainly on theme and date. In the World of Independent Culture[from: Tygodnik Mazowsze, no. 114 (24 January 1985)]This article in the underground weekly for the Warsaw region is based on a conversation with a member of the underground Committee for Independent Culture active under the auspices of the Solidarity leadership. The article describes the various forms of independent cultural activity that have been particularly popular since the imposition of martial law. Concerning Graphics[from: Kronika Malopolska, no. 58 (10 October 1984)]This is a review of an independent exhibition that took place last year in a church in Kraków. The exhibition was typical of numerous, similar events that take place throughout Poland. "Kronika Małopolska" [Chronicle of the Małopolska Region] has been appearing every two weeks since February 1982. Fewer Setbacks, More Books: A Talk with the Independent Publishing House NOWA[from: Vacat, no. 17/18 (May/June 1984)]This is an excerpted translation of an interview with a representative of the Polish underground publishing house. NOWA , the Polish acronym for Niezależna Oficyna Wydawnicza [Independent Publishing House], was founded in the autumn of 1977 and initiated what is today a widespread alternative book market. "Vacat," itself published by NOWA, is a monthly journal devoted to social and political matters and has been appearing in Warsaw regularly since December 1982. The Solidarity Archives[from: Tygodnik Mazowsze, no. 115 (31 January 1985)]The following interview in the major underground Solidarity weekly for the Warsaw area is with a representative of the underground publishing house NOWA about its plan to bring out a series of documents concerning events in recent Polish history. Subversive Philately / by Rowland Hilski[from: Verbum, no. 7 (1984)]This article concerns postage stamps printed in the undergound by Solidarity. "Verbum", which is published by the Mazowsze Solidarity Confederation (Polish acronym MKS), is edited by Juliusz Ostrowski and appears in Warsaw. NOWA - Video[from: CDN - Głos Wolnego Robotnika, no. 110 (19 April 1985)]This brief item in the Warsaw underground weekly [To Be Continued - Voice of the Free Worker] published by the Interfactory Workers' Committee since mid-1982 describes a new means of breaking through the censorship barrier: the underground publishing house NOWA has begun the mass production of video cassettes.